"It is All He Can Do to Cope with the Roads in His Own District": Labor, Community, and Development in Northern Ghana, 1919–1936*. (10th November 2017) - Wiemers, Alice
Abstract: In the 1920s and 1930s, colonial officials in Ghana's Northern Territories formulated the first development plans for this hinterland region. Administrators recast local roads and bridges as instruments of agricultural production and began to pursue small-scale resettlement efforts. In the absence of colonial funding, officials layered the requirements of development onto existing forced labor policies that took northerners to the cocoa- and gold-producing South. Using records from neighboring districts in the Northern Province, this article asks how demands for labor helped define the practice, experience, and limits of colonial authority. Intraregional mobility became a particular concern of officials as northerners began to "vote with their feet" to avoid forced labor. This article examines knotty cases in which questions of migration drew officials into local struggles to attract followers and manage the burdens of an extractive state. Northerners forced colonial officials to treat labor not just as something that could be extracted from bodies, but also as a political act involving subjects, chiefs, and officials. This article concludes in the early 1930s, when signers of the ILO's Forced Labour Convention formalized exceptions for labor that was demanded in the "direct interest of the community" or constituted "minor communal services." Far from eliminating state claims to labor, these initiatives increasingly enshrined them in emerging practices of development.